Role of the TMG flow rate on the GaN layer properties grown by MOVPE on (hkl) GaAs substrates. (October 2019) - Laifi, J.; Saidi, C.; Chaaben, N.; Bchetnia, A.; El Gmili, Y.; Salvestrini, J.P.
Abstract: The role of the TMG flow rate on the properties of the GaN layer grown by MOVPE on (001) and (11n)/n=2, 3 GaAs substrates were investigated. The surface morphology, crystalline quality and optical property were found to be strongly dependent on the TMG flow rate. As the latter decreased to 16 μmol/min, in-situ reflectance measurements showed a constant signal. This is attributed to the enhanced coalescence process, which resulted in the improvement of the surface morphology. A high TMG flow rate of 40 μmol/min sccm promoted predominantly vertical growth and resulted in the formation of a three-dimensional island. The lowest YL intensity and FWHM values of near band edge emission were obtained for GaN layers grown on (001) GaAs substrate with a TMG flow rate of 16 μmol/min, indicating an improvement of the optical properties of the GaN layer. This improvement is attributed to the coalescence process at the initial growth stage of GaN and the lateral growth process. All these behaviors were always observable whatever the used substrates. Depth resolved-CL showed that a mechanism of phase transformation in response to changing the substrate orientations.